Can Grants to Consortia Spur Innovation and Science-Industry Collaboration? Regression-Discontinuity Evidence from Poland - Bruhn, Miriam; McKenzie, David (Published by Oxford University Press on behalf of the World Bank, 2021)
Innovation policy aims to foster collaborations between science and industry in many countries, but there is little evidence for the effectiveness of such efforts in developing countries. We use regression discontinuity to measure the impact of funding from Poland’s In-Tech program on innovation activities carried out by consortia of firms and research entities. A detailed follow-up survey of applicants enables us to measure a wider variety of outcomes than typically used in the literature. We find that the grants increase the probability of a project being completed by almost 60 percentage points, lead to more science-industry collaboration, and increase the probability of domestic patents and publications related to the proposed project. We also find early effects on commercialization of products related to the proposed project.